RELATIONSHIP OF DEW POINT AND AMBIENT TEMPERATURE VARIATION ON WELD QUALITY - Sawrav, Kumar; Bandyopadhyay, Partha Pratim (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This investigation deals with the study of the effect of environmental parameters viz dew point temperature, relative humidity, ambient air temperature, and job surface temperature on robotic MAG (Metal active gas) welded joint quality. Weld samples taken were mass manufacturing welded structures of a heavy-large scale industry, which were further subjected to semi-automatic ultrasonic testing to assess defects within welded joints. The trend of defects observed and recorded after ultrasonic testing of weld joints was co-related with the trend of atmospheric parameters for a span of four years to establish a linear empirical relationship. It has been established that variations in atmospheric parameters resulted in variations in the trend of weld defects. These variations were studied to get the empirical relationship to establish the effect of variation in atmospheric parameters on weld quality or defects in joints. It has been observed that whenever there was a drop in the "difference in ambient air temperature & dew point temperature, especially less than 5", a drop in ultrasonic testing straight pass % was observed than the average value.